Pengembangan Mobile Learning pada Materi Transformasi Geometri untuk Menstimulasi Penalaran Matematis Siswa Kelas VIII - Amelia, Riska Putri; Rofiki, Imam (MATHEdunesa, 2025)
Mathematical reasoning can be influential in understanding learning materials. However, students’ mathematical reasoning skills are in the low category, especially in geometric transformation materials. This is due to the lack of learning media used by teachers. Therefore, this study aims to determine the process and result of developing mobile learning that is valid, practical, and effective. This research method is Research and Development (R&D) with the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation. The research began with observations and interviews followed by making a design in the form of storyboard. Mobile learning was constructed using Articulate Storyline 3 application integrated with TeacherMade App, GeoGebra, and Wordwall then implemented in learning. Evaluation was conducted at each stage to make improvements to the mobile learning. The participants of study involved 21 students of class VIII-C SMP Laboratorium UM as well as lecturers and teachers as validators. The instruments used were validation sheet, mathematical reasoning rubric, response questionnaire, and test questions. The result showed that mobile learning developed was valid with an average validity score for media of 3.53, material 3.35, technology of 3.66, and language of 3.25. Practicality test result based on student response questionnaires obtained an average score of 3.2 which indicates that mobile learning is practical, useful, and effective. The test results showed that 80.95% of students achieved more than KKTP based on mathematical reasoning with an average score of 80.24 so that mobile learning met the effectiveness criteria.